The Influence of Work Environment, Compensation, Career Development, and Employee Retention on Turnover Intention (Survey on Plastic Division Employees CV. Surya Nedika Isabella) - Suryani, Yeyen; Iskandar; Akbar, Ilham; Ibrahim, Muhamad Aksha Nur (International Journal Administration, Business & Organization, 2024)
The objective of this study is to investigate the impact of the work environment, salary, career development, and staff retention on turnover intention within the Plastic Division of CV. Surya Nedika Isabella. The study used a quantitative methodology, employing a saturated sample of 40 employees from this specific division. Information was gathered using a survey that employed an ordinal scale. The analysis was conducted using descriptive statistics and classical assumption tests, such as normality, multicollinearity, and multiple linear regression tests, through the SPSS 22 software. The results suggest that various factors, including the work environment, compensation, career development, and employee retention, collectively influence turnover intention. Specifically, the work environment has a significant and positive impact on turnover intention. Similarly, compensation also has a significant positive effect on turnover intention. Additionally, career development significantly and positively affects turnover intention. However, employee retention has a insignificantly impact positive on turnover intention.